2019
DOI: 10.14233/ajchem.2019.21697
|View full text |Cite
|
Sign up to set email alerts
|

Schiff Base Metal Complexes as Anticancer Agents

Abstract: Cutting-edge practices in bioinorganic chemistry are pivotal for enhancing the layout of compounds to lessen poisonous facet effect and recognize their mechanism of action. A powerful anticancer agent should own inherent, inhibitory property and also delivery, dosage and residence time in vivo. Organic function and conformation of mutated gene may be altered by way of binding of metal ions. Upswing of activities counting on the structural data, intending in enhancing and growing different forms of metal based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The Cu (II) complex showed enhanced cytotoxicity than other metal complexes from this work and is comparable with the IC 50 values of the cis-platin drug (20.2-22.4 μM) based on the literature. [76][77][78] The anticancer property of the metal complexes is depending on their DNA binding ability and causes damage/change in their structure, resulting in impairment of its function. The structural modifications/damage is followed by inhibition of replication and transcription process, eventually leading to cell death as the DNA lesions are not properly repaired.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…The Cu (II) complex showed enhanced cytotoxicity than other metal complexes from this work and is comparable with the IC 50 values of the cis-platin drug (20.2-22.4 μM) based on the literature. [76][77][78] The anticancer property of the metal complexes is depending on their DNA binding ability and causes damage/change in their structure, resulting in impairment of its function. The structural modifications/damage is followed by inhibition of replication and transcription process, eventually leading to cell death as the DNA lesions are not properly repaired.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…A mitochondrial enzyme in living cells, succinate-dehydrogenase, cleaves the tetrazolium ring, converting the MTT to an insoluble purple formazan. (15,16) Therefore, the amount of formazan produced is directly proportional to the number of viable cells.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Crystals of 3, 4 and 8 suitable for single-crystal X-ray diffraction analysis were obtained by dissolution in acetonitrile/2-propanol followed by slow evaporation of the solvent at room temperature. Crystallographic measurements for 3, 4 and 8 were collected with K-geometry diffractometers: Xcalibur R (Agilent Technologies, city, state abbrev if USA, country) with a Ruby CCD camera (3 and 4) and a Kuma KM-4 CCD with a Sapphire2 CCD camera (8), with graphite monochromatized Mo-Kα radiation (λ = 0.71073 Å) at 100(2) K, using an Oxford Cryosystems cooler. Data collection, cell refinement, data reduction and analysis were carried out with CrysAlisPro [33].…”
Section: Single Crystal X-ray Structure Determination Of 3 4 Andmentioning
confidence: 99%
“…Many studies have indicated the antitumor potential of isothiazole derivatives. CP-547.632 39, which belongs to the (3-aryl-4-carboxamido-isothiazol-3-yl)-carbamides, is a promising tyrosine kinase inhibitor with antineoplastic activity [7,8] used in the treatment of non-small cell lung cancer. CP-547.632 39 is an anti-angiogenic drug, which is effective only in combination with other cytostatics [9,10].…”
Section: Introductionmentioning
confidence: 99%